1997
DOI: 10.1016/s0029-7844(97)00392-x
|View full text |Cite
|
Sign up to set email alerts
|

Reversible fetal hydrops associated with indomethacin use

Abstract: Ultrasonographic screening for signs of constriction of the ductus arteriosus should be done within 48 hours of instituting indomethacin therapy at any gestational age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Maternal side effects include the prolongation of pregnancy and labor [6,7]. Reported adverse fetal side effects of indomethacin and other NSAIDs include constricted ductus arteriosus (DA) [3,[8][9][10][11][12], limb ischemia [13], hydrops fetalis [14,15], oligohydramnios, ileal perforation [16], and cystic brain lesions [17]. The possible teratogenic effects of NSAIDs used in early pregnancy include gastroschisis, associated with aspirin and ibuprofen [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal side effects include the prolongation of pregnancy and labor [6,7]. Reported adverse fetal side effects of indomethacin and other NSAIDs include constricted ductus arteriosus (DA) [3,[8][9][10][11][12], limb ischemia [13], hydrops fetalis [14,15], oligohydramnios, ileal perforation [16], and cystic brain lesions [17]. The possible teratogenic effects of NSAIDs used in early pregnancy include gastroschisis, associated with aspirin and ibuprofen [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies indicate that fetal ductal constriction following indomethacin treatment is usually reversible after cessation of the treatment, we hypothesize that in our case the heart had been overworked from the high‐output state and was too vulnerable to tolerate the extra afterload caused by indomethacin‐induced ductal closure, resulting in rapid development of cardiac failure and frank hydrops fetalis.…”
Section: Discussionmentioning
confidence: 74%
“…Diastolic and global function: Not assessed. Systolic dysfunction: All NSAIDs increased the PSV in the ductus arteriosus, indicating constriction which might also cause tricuspid regurgitation [17,28,35]. Furthermore, one of the two studies found decreased right ventricular fractional shortening probably associated with an increased ventricular inner end-diastolic diameter (Figure 2) [14,28].…”
Section: Nonsteroidal Anti-inflammatory Drug (Nsaid)mentioning
confidence: 99%